115 Atrial high rate episodes and atrial fibrillation burden: do they have similar association with cardiac remodelling?. (9th June 2011) - Khoo, C W; Krishnamoorthy, S; Dwivedi, G; Balakrishnan, B; Lim, H S; Lip, G Y H
Abstract : Background and Objectives: Contemporary pacemaker devices allow quantification of atrial high-rate episodes (AHREs) and atrial fibrillation burden (AFB) accurately. Cumulative ventricular pacing (Vp) is associated with development of atrial fibrillation, but it is not clear if AHREs and AFB share similar pathophysiologic associations with left atrium (LA) and ventricle (LV) function and remodelling. Methods: In total, 87 patients with dual-chamber pacemaker underwent two-dimension (2D) and tissue Doppler imaging (TDI) echocardiography. LA volume (LAV) was evaluated by area-length method and indexed to body surface area. Septal A′ was used to measured regional LA function. LV systolic and diastolic parameters were evaluated by mitral inflow velocity (E, A, E/A), LV ejection fraction (biplane Simpson's) and septal TDI velocity. The presence of AHREs (defined by atrial-rate ≥220 beats/min and ≥5 minutes) and AFB were derived from pacemaker diagnostics. Plasma markers of remodelling, matrix metalloproteinases-1 (MMP1) and tissue inhibitors of metalloproteinases-1 (TIMP1), were analysed by ELISA. Results: Baseline characteristics and comorbidities were comparable between groups (Abstract 115 table 1). Patients with AHREs had significantly larger indexed LAV (p=0.011) and higher cumulative Vp (p=0.012), but this was not associated with elevation of MMP1 and TIMP1. Plasma markers, LV systolic and diastolic parameters were comparable between groups. In patients with AHREs, the AFB ranged from 0 to 99% and correlated with E/A (r=0.966, p<0.001), and inversely correlated with late acceleration velocity (A) (r=−0.612, p=0.009). On linear regression analysis, A, E/A, septal A′ were independently associated with AFB (all p<0.01). Conclusion: Cumulative Vp and increased LAV are associated with the development of AHRE, but AFB is independently associated with changes in LA function and LV diastolic function. This study suggests AHREs and AFB have dissimilar pathophysiologic associations with left atrium and ventricle remodelling.